THE UNWED MOTHER AND SAMPLING BIAS. - Vincent, Clark E. (American Sociological Review)
Preliminary survey of the available data on unwed motherhood reveals that historically a variety of etiological factors have been emphasized. Studies made during the 1920's stressed such causal factors as "immorality" and "mental deficiency." During the 1930's findings pointed to factors of a "broken home," "poverty," "little education" and "domestic occupation." Within the past two decades, unwed motherhood has been explained increasingly as an accepted pattern of life in a given sub culture. However, the most frequent emphasis at the present time appears to be upon psychological processes. The majority of current studies conclude that unwed motherhood is a product of unresolved parent child conflict and represents an "unrealistic way out of inner difficulties." Equally evident from such a survey is the fact that in the majority of investigations reported, the samples of unwed mothers were taken from public institutions, welfare agencies or psychiatric clinics. This method of sampling has prolonged the picture of the unwed mother as being an extremely young, poor, uneducated or psychologically disturbed female. This sampling procedure is in part related to the ease with which such groups can be studied. It is also related to and in turn reinforces, a like causes like approach which tends to regard unwed motherhood as bad and then emphasizes bad or pathological etiological factors.